The Effect of Youtube Media Combine with Mind Mapping on The Material of Plant Tissue Structure and Function on MAN 2 Pati Student’s Knowledge - Didi Nur Jamaludin; Aizzatin Ulya (Jurnal Report of Biological Education, 2021)
This research is motivated by the importance of using effective learning media to increase students' knowledge. YouTube media, a combination of, is one of the media that can train imaginative power and play an active role in learning activities so as to develop students' knowledge. The purpose of the study was to determine the use, increase the quality of knowledge, and the effect of YouTube media combined mind mapping on students' knowledge of the structure and function of plant tissue. This research is a quasi-experimental research design with the matching only posttest only control group design. The population of this research is the students of class XI MAN 2 Pati totaling 189 students. The research sample was selected using a cluster random sampling technique, namely class XI IPA 1 and XI IPA 2. The research data was collected using tests and documentation. The data analysis technique used to test the hypothesis using the Mann Whitney test. The results showed that the use of youtube media combined with mind mapping in the experimental class had a good influence on students' knowledge of the structure and function of plant tissue with an average posttest value of 82.55 for the experimental class and 56.37 for the control class, indicating an influence on the quality of students' knowledge. on the structure and function of plant tissues. The results of the analysis of the hypothesis test obtained a significance value of <0.05 (0.000 <0.05) so it can be concluded that there is an influence of youtube media with a combination of mind mapping on students' knowledge of the plant tissue function and structure. Keywords : Youtube media, Mind Mapping, Plant Tissue Knowledge